An international cohort comparison of size effects on job growth - Michael Anyadike-Danes; Carl-Magnus Bjuggren; Sandra Gottschalk; Werner Hölzl; Dan Johansson; Mika Maliranta; Anja Myrann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
The contribution of different-sized businesses to job creation continues to attract policymakers' attention, however, it has recently been recognized that conclusions about size were confounded with the effect of age. We probe the role of size, controlling for age, by comparing the cohorts of firms born in 1998 over their first decade of life, using variation across half a dozen northern European countries Austria, Finland, Germany, Norway, Sweden, and the UK to pin down size effects. We find that a very small proportion of the smallest firms play a crucial role in accounting for cross-country differences in job growth. A closer analysis reveals that the initial size distribution and survival rates do not seem to explain job growth differences between countries, rather it is a small number of rapidly growing firms that are driving this result.
Keywords: L25; L26; E24; M13; 330; birth cohort; firm age; firm size; firm survival; firm growth; distributed micro-data analysis